ANALISIS KESALAHAN SISWA SMA KELAS XI PADA POKOK BAHASAN TRIGONOMETRI BERDASARKAN GENDER - Amalia, Rina; Sawitri, Wulan Yuni (Jurnal Karya Pendidikan Matematika, 2020)
This study aims to analyze the mistakes of class XI high school students on trigonometric subjects based on gender. The method used is descriptive qualitative. Samples and subjects in this study were taken by purposive sampling consisting of 5 female students and 5 male students of class XI. The results of the research error of male students are at the stage of understanding the problem, as well as at the stage of the problem solving process, where students are less able to show mathematical operations clearly and students are confused when getting symbols or numbers that they do not understand. While for female students the error lies in stage of understanding the problem, the thing that shows the ignorance is the lack of student understanding of the meaning of the terms or special symbols contained in the question.